Construction of Pisuke Standards for Marriage of the Lombok Sasak Tribe by the Sasak Paer Timuq (Maspati) Traditional Council in East Lombok Regency - Lalu Riki Wijaya; Marzuki; Lalu Supriadi bin Mujib (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Pisuke in the Sasak Tribe Traditional Marriage Process is an amount of money given by the man to the woman outside of her dowry, the purpose of which is twofold: first as a substitute for the costs of raising a daughter. Second, as a basis for men not to think that women's family status is too low. Before the establishment of the Pisuke tradition, the Sasak people, especially the East Lombok region, first knew the term change. In ancient times there were several levels of change agreed upon and determined by the Sasak Indigenous Community itself, namely: First, Utame Change (First Level), Second Madye Change (Middle Level), and Third, namely Indrie Change (Lower/Lower Level). Problem Formulations in this research include: 1). How is the construction of the Pisuke Determination of the Sasak Paer Timuq (Maspati) Traditional Council in the Marriage of the Sasak Lombok Tribe?; And 2). What is the typology for determining Pisuke standards in marriage between the Lombok Sasak tribe?. The method used in this research is a type of qualitative research. The data in this research was obtained from primary data obtained directly from informants, and then supported by secondary data in analyzing the research results.. Meanwhile, the research approach used is to use a sociological juridical approach, namely in dealing with problems discussed based on applicable regulations and then connected to the facts that occur in society. The results of this research show that the Pisuke tradition in the marriages of the Sasak tribe still tends to be determined based on the perspective of each family, which traditionally and institutionally the Sasak traditional council has not regulated this matter.